THE IMPACT OF FINANCIAL TECHNOLOGY (FINTECH) ADOPTION ON THE INCOME OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN TUGUMULYO DISTRICT - Nene Diana; Taufik Taufik; Agung Putra Reneo; Cean Maria Bella (LPPM STIE Muhammadiah Bandung, 2026)
The development of financial technology (fintech) has changed the way MSMEs conduct transactions while opening up wider access to financing. This study aims to analyze the effect of fintech on the income of MSMEs in Tugumulyo District, with fintech proxied by the use of peer-to-peer (P2P) lending services and the Indonesian Standard Quick Response Code (QRIS). This study uses a quantitative approach with a causal design. Primary data were collected through questionnaires distributed to 70 MSME owners who have adopted at least one fintech service. Data analysis techniques were performed using multiple linear regression, accompanied by classical assumption tests, simultaneous tests (F-tests), partial tests (t-tests), and determination coefficients. The results of the study indicate that P2P lending and QRIS together have a significant effect on MSME income. Meanwhile, in part, P2P lending has been proven to have a positive and significant effect on MSME income, suggesting that digital-based financing access enhances capital capacity and business activities. QRIS also shows a positive and significant effect on MSME income, reflecting improved transaction efficiency and payment convenience for consumers. These findings confirm the strategic role of fintech adoption in increasing MSME income through operational efficiency and inclusive financial access. These findings contribute empirical evidence to the literature by highlighting the role of fintech in improving MSME income within a semi-rural context, which remains underexplored in prior studies.